Hymne an Numušda. Kritik und Versuch einer Interpretation - Sauren, Herbert
VS 17,38, bearbeitet von A. Falkenstein, SAHG 112-114; Ä. Sjöberg, OrS 22 (1973) 107-116; M.-A. Dupret, Or 43 (1974) 327-343.